2017
DOI: 10.1038/s41598-017-15941-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host DEAD-box RNA helicases that regulate cellular tropism of oncolytic Myxoma virus in human cancer cells

Abstract: Myxoma virus (MYXV), a Leporipoxvirus, is being developed as an oncolytic virotherapeutic for the treatment of a variety of human cancers. MYXV tropism for human cancer cells is largely mediated by intracellular signaling networks that regulate viral replication or innate antiviral response pathways. Thus, MYXV is fully or partially permissive for the majority of human cancer cells that harbor defects in antiviral signaling, but a minority are nonpermissive because the virus infection aborts before its complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 47 publications
2
46
0
Order By: Relevance
“…Biochemical studies of HIV-Rev, alone or Rev in combination with RRE RNA, have also identified positive roles for DDX3X, DDX5, DDX17, and DDX21 in HIV infection, although some of these interactions could be indirect [84]. Other DEAD-box helicases have been found genetically by screening to identify genes that affect infection [41,88]. The genetic screening of DEAD-box helicases in poxvirus infection revealed both positive and negative regulation of infection by DEAD-box helicases [88].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biochemical studies of HIV-Rev, alone or Rev in combination with RRE RNA, have also identified positive roles for DDX3X, DDX5, DDX17, and DDX21 in HIV infection, although some of these interactions could be indirect [84]. Other DEAD-box helicases have been found genetically by screening to identify genes that affect infection [41,88]. The genetic screening of DEAD-box helicases in poxvirus infection revealed both positive and negative regulation of infection by DEAD-box helicases [88].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Other DEAD-box helicases have been found genetically by screening to identify genes that affect infection [41,88]. The genetic screening of DEAD-box helicases in poxvirus infection revealed both positive and negative regulation of infection by DEAD-box helicases [88]. And still other studies have focused on changes in gene expression that indicate either cellular innate immune responses or a viral manipulation of the host cell environment [31,89,90].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a RNA helicase, DDX5 was shown to be a pro-viral host factor in biosynthesis of several RNA viruses, including HIV and HCV (42). By contrast, DDX5 has antiviral function in myxoma virus biosynthesis (43) and in HBV biosynthesis, by a mechanism not yet understood (7). In our earlier studies, we have observed that DDX5 protein levels become progressively reduced in HBV replicating/infected hepatocytes.…”
Section: Discussionmentioning
confidence: 88%
“…However, DHX9 and DHX36 have also been shown to act as DNA helicases (Linder, 2006; Zhou et al, 2003). The role of DHX9 as an RNA or DNA helicase has been studied in the context of cancer such as colorectal and lung cancer, where DHX9 regulation is cancer-specific (He et al, 2017; Mi et al, 2016; Rahman et al, 2017; Sun et al, 2014). It is also known that DHX9 binds to viral dsRNA in myeloid dendritic cells, leading to the activation of NF-κB and IRF3, along with the production of IFN-α/β (Zhang et al, 2011d).…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%